Students’ motives for restricting academic freedom: Viewpoint discrimination and prosocial concerns - Claudia Diehl; Matthias Revers; Richard Traunmüller; Nils B. Weidmann; Alexander Wuttke (Proceedings of the National Academy of Sciences, 2025)
We advance the understanding of so-called “cancel culture” at the university by presenting the results of three survey experiments among university students. Designed in an “adversarial collaboration” among researchers with competing perspectives, these experiments disentangle whether students’ preferences for curtailing academic freedom are based on viewpoint discrimination, professional academic standards, or prosocial concerns. Our findings show that a substantive share of university students support viewpoint-based restrictions on academic discourse. While they also apply academic and prosocial criteria, they apply them more strongly to conservative viewpoints. The results further show that conservative statements are perceived as causing more social harm. However, prosocial concerns do not fully explain the higher demand for ideological viewpoint discrimination. These results are important because they can inform the debate about universities as ideological spaces—a view often invoked in recent government-led attacks on academic freedom.